Effects of probiotics in swines growth performance: A meta-analysis of randomised controlled trials - Zimmermann, Jorge Alberto; Fusari, Marcia Lucia; Rossler, Eugenia; Blajman, Jesica E.; Romero Scharpen, Analía; Astesana, Diego Martín; Olivero, Carolina Raquel; Berisvil, Ayelén Patricia; Signorini, Marcelo; Zbrun, María Virginia; Frizzo, Laureano Sebastian; Soto, Lorena Paola (2018)
The objective of this meta-analysis was to assess effects of probiotics on the growth performance of pigs (Average Daily Gain (ADG) and Feed Efficiency (FE)). Data bases (i.e. PubMed, ScienceDirect, and Scopus) were searched from 1980 to 2015 unrestricted by language. The inclusion criteria were: randomised and controlled experiments using pigs without apparent disease and published in peer reviewed journals. Sixty-seven and 60 experiments were included to assess probiotic effects on ADG and FE, respectively. LAB supplementation increased ADG (difference in mean (DM) = 29.930 g/day, 95% confidence interval (CI) 17.617–42.261) and improve feed efficiency (DM = −0.096 kg feed/kg body weight, 95%CI −0.120–0.071), considering the source of heterogeneity. There were no evidence of publication biases. The meta-analysis showed that application of probiotics during the first stage of pig grown and in the finishing period resulted in greater ADG and FE. The effect was not related to the use of mono-strain or multi-strain probiotics, although it may depend on the strain used. The breeds (especially F1 and three-breed-rotational crossbreeding) and the characteristic of these breeds (maternal breeds) included in the experiments had an impact on the outcomes. These results might be used to define the guidelines to standardize the experimental designs of future trials and to include the impact of each covariate on the differences in the estimated effect sizes.